In vitro Cell Viability and Microbial Challenge Testing of Camellia sinensis Green Tea and Myristica fragrans Nutmeg Based Phyto Topical Applicant Against the Pyogens Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans - Kulandhaivel, M (International Journal of Pharmaceutical & Biological Archive, 2012)
In vitro Cell Viability and Microbial Challenge Testing of Camellia sinensis Green Tea and Myristica fragrans Nutmeg Based Phyto Topical Applicant Against the Pyogens Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans